STRUKTUR SOSIAL, STRATEGI NAFKAH, DAN TINGKAT KESEJAHTERAAN NELAYAN PASCA REKLAMASI TELUK JAKARTA : Social Structure, Livelihood Strategy, and Fishers' Welfare in the Post-Reclamation of North Jakarta Coast - Querdiola, Cisilia; Kinseng, Rilus A; Gandi, Rajib (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2023)
Reclamation can be a source of social changes in fishing communities. This study aims to analyze the social structure, strategies for earning a living, and the level of welfare of the fishing community in Cilincing Fishers’ Village, North Jakarta during the post-reclamation period. The research was conducted using both quantitative and qualitative methods. Quantitative data were obtained by distributing questionnaires and then processed using the Paired-Sample T-test and the Wilcoxon Signed Ranking Test. Qualitative data were obtained through in-depth interviews with informants. The results showed that the social structure of fishers in Cilincing remained the same before and after reclamation. In terms of the social associative process, there are significant differences between before and after reclamation. After-reclamation, there has been an increase in various togetherness activities such as cooperation, mutual assistance, and deliberation. In terms of livelihood strategies, some fishers have experienced changes after reclamation, for example by doing side jobs. From the welfare level, both catch and income experienced a significant decline. Keywords: fishers, livelihood strategy, reclamation, social structure, welfare.